Studi Pemberdayaan Masyarakat Dengan Zakat Community Development Di Baznas Kabupaten Jember - Noviana Elisca; Abdullah Faqih; Mohammad Misbah Haqki (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Community Empowerment Study with zakat community development is a new paradigm in zakat distribution which aims to empower poor and marginalized communities. This method offers a unique solution by combining the principles of zakat with the principles of community development which can effectively reduce poverty and improve community welfare. In this study, the author will review various cases and literature studies that have been carried out to prove the effectiveness of using community development zakat in community empowerment efforts. The study results show that community development zakat can be a very effective instrument in alleviating poverty and improving the standard of living of marginalized communities. Apart from that, this study also shows that community development zakat has a wider positive impact on society, both in economic, social and spiritual terms. Therefore, it is hoped that the use of community development zakat can be a more holistic and effective alternative in distributing zakat and provide a significant contribution to more sustainable community development.